TANGGUNG JAWAB ORANG TUA TERHADAP ANAK PASCA TERJADINYA PERCERAIAN ORANG TUA (MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM) - MASYITAH DWI AJENG WIRAPUSPA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Runtung2. Muhd. Yamin3. Utary Maharany Barus However, a marriage may end with a divorce on its way; thus, its purpose cannot be accomplished. The consequence of a divorce is responsibility of the parents. In spite of a divorce, the children’s rights should remain protected. Parents’ responsibility after a divorce is a very important thing for the survival of the minors who cannot take care of themselves yet, regarding their property or their own lives; or, in other words, they are incompetent of taking legal action. Based on this background, there were three problems in this research, i.e. what legal consequence children got after their parents had been divorced, what responsibilities parents had for their children’s civil rights after the divorce, and how their responsibility for their children was supervised after the divorce.The research used descriptive analytic and judicial normative design using statue approach which described, analyzed, and explained the regulations about Legal Consequence on Children after divorce, Parents’ responsibility for Children’s Civil Rights and Parents’ Responsibility Supervision on Children after divorce.Keywords: Parents’ Divorce, Parents’ Responsibility after Divorce, Right to Child Custody